Polskie produkty turystyczne i ich e-promocja - Janik, Marcin; Szwichtenberg, Aleksander (Polish Tourist Products and Their E-Promotion, 2005)
In article were analysed activities they have to aim promotion of polish tourism product at Internet. In particular products based on polish cultural objects from the World Heritage List of UNESCO. From 9 investigated internet sites, three have been really useful for tourists.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 195-200